Let power series solution of given differential equation be "y= \\sum_{n=0}^{\\infin} c_nx^n" .
"\\implies y'= \\sum_{n=1}^{\\infin} nc_nx^{n-1}" .
By putting in given differential equation, we got
"\\sum_{n=1}^{\\infin}n c_nx^{n-1}+ \\sum_{n=0}^{\\infin} c_nx^n = 1"
"\\implies \\sum_{n=0}^{\\infin}(n+1) c_{n+1}x^{n}+ \\sum_{n=0}^{\\infin} c_nx^n = 1 \\\\\n\\implies \\sum_{n=0}^{\\infin}((n+1) c_{n+1}+c_n)x^{n}=1"
Now, by comparing the coefficient on both sides we get,
"c_1+c_0 = 1 , \\ and \\ (n+1) c_{n+1} + c_n = 0 \\ \\forall n\\geq 2 \\implies c_{n+1} = -\\frac{c_n}{n+1}"
"\\implies c_1=1-c_0, c_2 =- \\frac{c_1}{2} = \\frac{c_0-1}{2}, c_3 = \\frac{c_2}{3} = \\frac{c_0-1}{3!}, c_4= \\frac{c_0-1}{4!}" and so on.
So, power series solution of given differential equation is
"y= c_0+(1-c_0)x + \\frac{c_0-1}{2!} x^2 + \\frac{c_0-1}{3!} x^3+ ..."
Comments
Leave a comment